Active Rheology Control of Cementitious Materials. - De Schutter, Geert. (Modern Concrete Technology Series, 2023)
Open Access at www.routledge.com from SmartCast ERC Advanced Grant Project, this outlines rheology & stiffening control methods for controlling the rheological &stiffening behaviour of fresh self-compacting concrete during casting, by modifying the concrete with responsive superplasticizer or magneto-responsive mineral additions.